The rise of Housing Nationalism in Canada and transnational property ownership patterns. - Lauster, Nathanael; von Bergmann, Jens (Journal of Ethnic & Migration Studies, 2025)
We consider how housing acts as a potential realm where perception of crisis can activate reactionary nationalism, investigating how it differs from and interacts with other realms (e.g. jobs and wages, crime, and social welfare). We argue that housing produces distinct triggers for reactionary responses, and potentially results in different media framing, politics, and policy trajectories. We detail the rise of Housing Nationalism in Canada, following its spread from British Columbia, where we find that flexible framing of foreign threat often borrowed from other realms. By contrast, pinning Housing Nationalism to policy generally required more tractable definitions of foreignness, tied to surveillance and the application of penalties. We examine the roll out of policy responses associated with Housing Nationalism and lay out potential harms in terms of challenges to liberal ideals, including Canadian multinationalism, immigrant incorporation, and transnational ties. Finally we provide a baseline of Canadian transnational property ownership patterns, demonstrating that within the provinces where Housing Nationalism became most dominant, Canadian residents generally own far more properties abroad than the number of properties owned in Canada by residents elsewhere. Overall, the Canadian case demonstrates the utility of considering housing as a distinct realm motivating the rise of reactionary nationalism.